PENGARUH KECERDASAN EMOSIONAL TERHADAP KINERJA PEGAWAI DI ORGANISASI PERANGKAT DAERAH - Frans Sanjaya (Laboratorium Jurusan Ilmu Administrasi Negara Fakultas Ilmu Sosial Universitas Negeri Padang, 2019)
This study aims to determine the contribution of emotional intelligence on the performance of employees in the District Device Organization of Tanah Datar Regency. The background of this study was the finding of problems in the emotional intelligence of employees that were not good in the District Device Organization of Tanah Datar Regency. This type of research is a quantitative research whose population is all civil servants in the area of the regional apparatus of Tanah Datar regency totaling 1.596 people. The sample in this study consisted of 320 respondents who were determined using the Slovin formula with an error rate of 5% and sampling was done through Multi Stage Random Sampling technique. Data collection in this study uses a questionnaire with Likert scale measurement.Data of this study were analyzed with linear regression test. The results showed that there was a contribution between emotional intelligence to employee performance by 22,9%. So it can be concluded that emotional intelligence contribute significantly to employee performance.